992 Time trends in work-related injuries in qatar: an analysis of hospital trauma registry data. (1st September 2016) - Mehmood, Amber; Consunji, Rafael; Peralta, Ruben; Abdelhamid, Rania; El-Menyar, Ayman; Allen, Katharine A; Malik, Shahnaz; Thomas, Sam; Al-Thani, Hassan; Hyder, Adnan
Abstract : Background: Work-related injuries (WRIs) are a leading cause of hospital visits in Qatar. Little is known about the burden of hospital admissions due to work related injuries. This study analysed hospital based trauma registry data for past seven years to understand the burden and outcome of these patients. Methods: A retrospective analysis of data from 2008-2014 was conducted on patients admitted to the Hamad Medical Corporation (HMC) Trauma Centre, the national trauma referral centre, and its mortuary with severe WRIs. These were defined as those suffered during working hours or while travelling to or from work and severe enough to need admission to the hospital; poisoning or heat related illnesses were excluded. Temporal trends in the burden, external causes of injuries and mortality rates were analysed. Results: A total of 3, 980 severe WRIs were recorded during the study period. Most workers were males (93.4%) with a mean age of 29.3 years. Almost all workers (98%) were expatriates. Occupation was known for only 37.5% of cases, and out of those 80% were general labourers. Over 39% of all WRIs were transport injuries. Other important causes were falls (25%) and exposure to inanimate mechanical forces (14%). During the study period, severe WRI rates declined from 50.24 to 31.64 per 100, 000 registered workers. Overall in-hospital mortality was 12.9%, with a decline from 15.5% to 9.6% between 2008 and 2014. The most common cause of WRI fatality was falls (49.5%). Conclusions: Severe WRI incidence and in-hospital mortality rates have been reduced by almost 40% in the past 7 years in Qatar. However, we need to also document the burden and outcomes of less severe WRIs and those seen and treated by other providers. Further studies are needed to determine the true burden of work-related injuries in Qatar, with a focus on unifying national WRI data in order to better inform strategies for occupational safety and injury prevention. Road safety for workers must be a priority in Qatar.